Public-private Partnerships As A Tool For Modern Public Management And Improving The Efficiency Of Algeria's Health-care System - Sedjel, Abdelmadjid; Mokhtari, Faiçal (جامعة الوادي - University of Eloued, 2022)
The study seeks to comprehend how the health system is reformed and its efficiency increased by utilizing the method of collaboration between the public and private sectors, as well as the principles of modern public management. The purpose of the study was to clarify the nature of the partnership between the public and private sectors, as well as the modern public management concept. It also highlights the various problems that Algeria's current health system faces because of the traditional model of public management, which does not consider cost and quality as efficiency and effectiveness criteria. Finally, we conclude that there is a third option that combines the public sector's financial, logistical, and institutional capabilities with the private sector's rationality and competitiveness
مقال
Keywords: Health System ; Modern Public Management ; PPP System